Family Self-Care in Chronic Disease Management: An Evolving Care Pattern? - Teresa Dionísio Mestre RN, MSc, PhD student; Ermelinda Valente Caldeira PhD; Manuel José Lopes PhD (SAGE Open Nursing, 2024)
Introduction Self-care emerges in the family context, despite being seen as an individual determinant of health. The family, understood as a system and social unit, converges to a pattern of self-care and not to a sum of it, assuming relevance at certain moments of the life cycle, particularly in the management of chronic disease. Purpose To perform the transposition of individual self-care to the family self-care, considering the current family's needs and characteristics, by adopting family self-care as the core concept of a care pattern as a determinant of family health. Conclusion The family unit is the most influential factor in the health status of individuals, and it will be through family self-care behaviors that families can be healthier by managing their diseases more effectively. They seek to achieve family health, maintaining health through health promotion and disease management practices, always mediated by family self-care behaviors.